Endosymbionts in spiders: driving force or hitchhikers? - Hundertmark, Antje (2019)
Endosymbionts such as Wolbachia and Rickettsia and their effects on their hosts have been extensively studied. In recent years these endosymbionts have gained attention as potential drivers of speciation by inducing reproductive isolation in differentially infected host populations. Research in this area has so far provided support for, as well as against, this theory. Whilst a plethora of studies exist on endosymbiont infections in insects, the knowledge about the effect of endosymbionts on spiders is still limited. Only a few studies so far could attribute observed sex ratio distortions and incompatibilities to the presence of one or more endosymbiont species. The work presented in this thesis aimed to further our understanding of endosymbiont infections in spiders and the role of endosymbionts in the speciation process.